2015
DOI: 10.1002/pbc.25485
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral white matter fractional anisotropy and tract volume as measured by MR imaging are associated with impaired cognitive and motor function in pediatric posterior fossa tumor survivors

Abstract: DTI provides a method for quantification of WM damage by tumor and by therapy-associated effects in survivors of pediatric posterior fossa tumors. DTI-derived WM integrity may be a representative marker for cognitive and motor deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…Neuroimaging studies in survivors of pediatric brain tumor have found reduced white matter integrity in specific tracts ( Aukema et al, 2009 ; King et al, 2015b ; Mabbott et al, 2006 ; Palmer et al, 2012 ; Riggs et al, 2014 ; Rueckriegel et al, 2010 ; Smith et al, 2014 ) and that the integrity of these tracts is associated with performance on neurocognitive measures of processing speed, motor speed, full scale IQ, fine motor function, working memory, memory, and executive functioning ( Aukema et al, 2009 ; Brinkman et al, 2012 ; Law et al, 2011 ; Palmer et al, 2012 ; Riggs et al, 2014 ; Rueckriegel et al, 2015 ). These studies suggest that structural changes to white matter may represent the neurobiological underpinnings of outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies in survivors of pediatric brain tumor have found reduced white matter integrity in specific tracts ( Aukema et al, 2009 ; King et al, 2015b ; Mabbott et al, 2006 ; Palmer et al, 2012 ; Riggs et al, 2014 ; Rueckriegel et al, 2010 ; Smith et al, 2014 ) and that the integrity of these tracts is associated with performance on neurocognitive measures of processing speed, motor speed, full scale IQ, fine motor function, working memory, memory, and executive functioning ( Aukema et al, 2009 ; Brinkman et al, 2012 ; Law et al, 2011 ; Palmer et al, 2012 ; Riggs et al, 2014 ; Rueckriegel et al, 2015 ). These studies suggest that structural changes to white matter may represent the neurobiological underpinnings of outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 This association is supported by previous studies, showing that fine motor abilities required to carry out this task can be severely damaged in patients who develop spinocerebellar ataxia and tend to correlate with cerebellar afferent connection volume. 23,51 A negative association was found between the PI of the right DRTC tract and the theory of mind task, which represents the ability to understand others' mental states. 24,25 As the PI expresses water anisotropic diffusion on a given plane, we could also interpret its value as a measure of the diffusion of water molecules on that plane.…”
Section: Correlation With Cerebellar Tracts According To Dti Tractogrmentioning
confidence: 98%
“…[19][20][21] However, the possible association between specific cerebellar tracts and neuropsychological functions has not been fully assessed, because the majority of these studies lack a comprehensive cognitive and neuropsychological evaluation and are mainly focused on motor abilities or selective neurocognitive domains, such as executive functions and working memory. 22,23 This is a pilot study designed to understand if DTI-based tractography could be able to identify possible correlations between cerebellar WM structure and cognitive outcome in children on long-term followup for PF tumors who were thoroughly assessed for neuropsychological functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that measure changes in white matter volume have shown that decrease in white matter volume following radiotherapy correlates with IQ decline and neurocognitive decline (46)(47)(48)(49). Voxel based morphometry approaches show that frontal white matter (especially right sided) is more sensitive to volume loss than other parts of the brain (48).…”
Section: Importance Of White Matter Structures On Neurocognitive Declinementioning
confidence: 99%
“…Studies have shown that development in cognitive function in children and adolescents correlates with an increase of FA (66,67). Studies looking at the effect of radiotherapy on white matter tract integrity have shown a reduction in FA in white matter of children treated with radiotherapy and this decrease in FA correlates with IQ, tests of neuropsychology function, and school performance (45,49,(68)(69)(70)(71). The decrease in FA is more noticeable with earlier age radiotherapy and increased radiotherapy dose (68,(70)(71)(72)(73).…”
Section: Diffusion Tensor Imaging Of White Matter Integritymentioning
confidence: 99%